2020
DOI: 10.1021/acsapm.9b01095
|View full text |Cite
|
Sign up to set email alerts
|

Quantity or Quality: Are Self-Healing Polymers and Elastomers Always Tougher with More Hydrogen Bonds?

Abstract: Polymer materials containing dynamic bonds have many potential applications including adhesives, elastomers, and coatings with long lifetimes. Interpenetrated networks (IPNs) were studied, where one network had covalent linkers, and the other network had dynamic quadruple-hydrogen-bonded 2-ureido-4­[1H]-pyrimidinone (UPy) linkers. IPNs typically have superior mechanical properties to each component network. IPNs had either nonpolar poly­(ethyl acrylate) (PEA) or hydrogen-bond-rich poly­(2-hydroxyethyl acrylate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 38 publications
(92 reference statements)
2
39
0
Order By: Relevance
“…The TRGO not only improved the mechanical performance but achieved a self-healing efficiency up to 85% at room temperature without applying external stimuli compared to pristine ENR. The improved healing efficiency was attributed to the presence of H-bonding interaction.Cummings et.al [132] 2020, suggested that quality of H-bond, i. e., strong and dynamic H-bonds have to be considered for applications that demand high mechanical performance even at the potential expense of total H-bonds (quantity). The authors considered interpenetrated networks (IPNs), with both covalent cross-links and dynamic quadruple-hydrogenbonded 2-ureido-4[1H]-pyrimidinone (UPy) linkers.…”
Section: Hydrogen-bonding In Self-healing Materialsmentioning
confidence: 99%
“…The TRGO not only improved the mechanical performance but achieved a self-healing efficiency up to 85% at room temperature without applying external stimuli compared to pristine ENR. The improved healing efficiency was attributed to the presence of H-bonding interaction.Cummings et.al [132] 2020, suggested that quality of H-bond, i. e., strong and dynamic H-bonds have to be considered for applications that demand high mechanical performance even at the potential expense of total H-bonds (quantity). The authors considered interpenetrated networks (IPNs), with both covalent cross-links and dynamic quadruple-hydrogenbonded 2-ureido-4[1H]-pyrimidinone (UPy) linkers.…”
Section: Hydrogen-bonding In Self-healing Materialsmentioning
confidence: 99%
“…The 25% re‐healing could be due to the supramolecular H‐bond interactions in the HEA moieties in the network. [ 50 ] PHEA–2.5%TMSDA materials showed moderate re‐healing properties, and ≈75% maximum recovery of the mechanical property was achieved with the best‐healed sample (Figure S9, Supporting Information). This decrease in healing efficiency in comparison to PHEA–1.25%TMSDA materials can be attributed to the increase in rigidity and less chain mobility in more crosslinked PHEA–2.5%TMSDA network.…”
Section: Resultsmentioning
confidence: 99%
“…The introduction of the DAM/PEEL network into the PSA system increased the toughness by nearly 9.24 MJ/m 3 , which was approximately 2.6 times that of PSA (~3.6 MJ/m 3 ) because of the increase in material toughness caused by the DAM‐PEEL network. This suggests that the increase in toughness originates from the increasing energy dissipation through physical cross‐linking in PSA/DAM‐PEEL dual cross‐linking networks 55 . Generally, a higher cross‐linking density leads to an improved tensile strength, which is accompanied by a decreased elongation at break 35,56 .…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the increase in toughness originates from the increasing energy dissipation through physical crosslinking in PSA/DAM-PEEL dual cross-linking networks. 55 Generally, a higher cross-linking density leads to an improved tensile strength, which is accompanied by a decreased elongation at break. 35,56 However, in this study, the introduction of a DAM/PEEL network into a PSA system simultaneously increased both the tensile strength and elongation at break.…”
Section: Mechanical Properties Of Psa/ Dam-peel Dual Cross-linking mentioning
confidence: 99%